2014
DOI: 10.2478/s11658-014-0186-4
|View full text |Cite
|
Sign up to set email alerts
|

Myricetin blocks lipoteichoic acid-induced COX-2 expression in human gingival fibroblasts

Abstract: Abstract:Periodontitis is an infectious disease caused by microorganisms present in dental bacterial plaque. Lipoteichoic acid (LTA) is a component of the external membrane of Gram-positive bacteria. It causes septic shock. Ingested flavonoids have been reported to directly affect the regulation of cyclooxygenase-2 (COX-2) expression induced by bacterial toxins. In this study, we examined the effects of four flavonoids (luteolin, fisetin, morin and myricetin) on the activation of ERK1/2, p38 and AKT, and on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Early studies in various literatures suggested it has the aptitude in reducing COX-2 expression in cancer [ 62 66 ] or noncancerous cell [ 67 , 68 ]. Myricetin is a widely distributed flavonol that is found in many plants, including tea, berries, fruits, vegetables, and medicinal herbs attenuated the COX-2 expression UVB-induced skin cancer [ 69 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Early studies in various literatures suggested it has the aptitude in reducing COX-2 expression in cancer [ 62 66 ] or noncancerous cell [ 67 , 68 ]. Myricetin is a widely distributed flavonol that is found in many plants, including tea, berries, fruits, vegetables, and medicinal herbs attenuated the COX-2 expression UVB-induced skin cancer [ 69 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, panduratin A suppresses gingival inflammation and osteoclastogenesis by inhibiting at least one pathway, MAPK, in LPS-stimulated HGF-1 and RANKL-treated RAW 264.7 cells. Previous studies reported several natural MAPK pathway inhibitors on periodontal inflammation from medicinal plants [25,26]. Although myricetin, luteolin, morin, and fisetin have been shown to reduce MAPK protein expression in periodontal cell lines, these natural compounds were used at a higher concentration than that of panduratin A [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of ERK-1/2, AKT and p38, and lipoteichoic acid-induced COX-2 expression in human gingival fibroblasts was inhibited by the compound. It also blocked IκB degradation and PGE2 synthesis and expression [ 127 , 128 ]. Myricetin did not have any effect on cell viability, but decreased the mRNA expression and enzyme activity of MMP-1, -2 and -8 in human growth factor (HGF).…”
Section: Pharmacological Applicationsmentioning
confidence: 99%